An experimental EEG study of brain activities underlying the Autonomous Sensory Meridian Response - Ali Mohammadi; Sahar Seifzadeh; Fatemeh Torkamani; Sina Salehi (IBRO Neuroscience Reports)
Autonomous Sensory Meridian Response (ASMR) is an audio-visual phenomenon that has recently become popular. Many people have reported experiencing a tingling-like sensation through their body while watching audio/video clips known as ASMR clips. People capable of having such experiences have also reported improved overall well-being and feeling relaxed. However, the neural activity underlying this phenomenon is not yet well-studied. The present study aims to investigate this issue using electroencephalography (EEG) employing an exploratory approach. We recorded resting-state EEGs from twelve participants before and after watching an ASMR clip and a control video clip. We divided the participants into two groups capable of experiencing ASMR tingling (ASMR group) and not capable of experiencing ASMR tingling (Non-ASMR group), by performing “Jenks Natural Breaks” clustering method on the results of a self-report questionnaire. We calculated the spectral power of EEG recording and compared the resulting values between the groups and sessions. We demonstrated a decline in the power of EEG activities in the delta frequency band in all regions of the brain and an increase in alpha activity in the occipital area of the brain and increases in beta oscillations was noted over the left fronto-temporal region of the brain among ASMR group. We did not observe similar results among the Non-ASMRs participants or among ASMRs in the control group.